Meaning diminished toward metaphysically modest semantics - Taylor, Kenneth Allen 1954-2019 (Oxford University Press, 2019)
"Meaning Diminished examines the complex relationship between semantic analysis and metaphysical inquiry. Kenneth A. Taylor argues that we should expect linguistic and conceptual analysis of natural language to yield far less metaphysical insight into what there is - and the nature of what there is - than many philosophers have imagined. Taking a strong stand against the so-called linguistic turn in philosophy, Taylor contends that philosophers as diverse as Kant, with his Transcendental Idealism, Frege, with his aspirational Platonism, Carnap with his distinction between internal and external questions, and Strawson, with his descriptive metaphysics, have placed too much confidence in the ability of linguistic and conceptual analysis to achieve deep insight into matters of ultimate metaphysics. He urges philosophers who seek such insight to turn away from the interrogation of language and concepts and back to the more direct interrogation of reality itself. In doing so, he maps out the way forward toward a metaphysically modest semantics, in which semantics carries less weighty metaphysical burdens, and toward a revisionary and naturalistic metaphysics, untethered to the a priori analysis of ordinary language."-- Provided by publisher.